PENGARUH ADANYA CLOSED CIRCUIT TELEVISION (CCTV) TERHADAP KINERJA PENGAWASAN DAN PELAYANAN UNIT APRON MOVEMENT CONTROL (AMC) DI BANDAR UDARA INTERNASIONAL ADI SOEMARMO SURAKARTA - Nurul Amalia Annisa; Lusiana Dewi Kusumayati; Yuyun Suprapto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The Adi Soemarmo International Airport Surakarta has 15 parking stands where some stands can be controlled from the Apron Movement Control office immediately. One of the main duties of the Apron Movement Control is to supervise every movement of vehicle, personnel, and item on the airside. This is the basic reason of the lack of the Apron Movement Control performance in conducting the supervision. Improving the supervision of the Apron Movement Control personnel and the CCTV in terms of surveillance can reduce violations. In addition, socialization on the importance of using high-visibility safety apparel has to be given to the personnel who work in the apron area. Moreover, the Closed Circuit Television that is connected to the Apron Movement Control office and periodic inspection by the Apron Movement Control can reduce violations in the airside.